Culling Layer Hen Ectoparasite Detection Sold at Wonokromo Market Surabaya City - Nashihatus Sholihah; Sherbina Bai; Sri Hidanah; Dhandy Koesoemo Wardhana; Agus Sunarso; Poedji Hastutiek; M.Gandul Atik Yuliani (Journal of Parasite Science (JoPS), 2022)
The purpose of the research were to identify the species, prevalence, and predilection of ectoparasite in Culling Layer Hen at Wonokromo Market, Surabaya City. The research was conducted from March to May 2021 with total of 100 sample of chickens were examined by the skin and feather body region. Identification of ectoparasite was carried out at The Laboratory Parasitology, Faculty of Veterinary Medicine Universitas Airlangga using permanent mounting methods. The results showed, the species of ectoparasite that infest the culling layer hen were Menopon gallinae 21%, Lipeurus caponis 10%, Ornythonissus bursa 10%, and Dubininia melopsitacci 70%. Predilection of ectoparasite shows that M. gallinae were found in the head-neck, back, wings, and legs region. L. caponis was found in the head-neck, wings, and back region. O. bursa was found in the legs and tail region, and D. melopsitacci was found in the entire body of chicken, the head-neck, back, wings, abdomen, legs, and tail.